2009
DOI: 10.1016/j.comnet.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of large-scale distributed systems – A topological view

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The algorithms covered thus far exactly find cut vertices without localization. In this study, we omit the probabilistic cut vertex detection algorithms given in [8,10,11,14,16] and localization-based cut vertex detection algorithms given in [13,15].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithms covered thus far exactly find cut vertices without localization. In this study, we omit the probabilistic cut vertex detection algorithms given in [8,10,11,14,16] and localization-based cut vertex detection algorithms given in [13,15].…”
Section: Related Workmentioning
confidence: 99%
“…The detection of cut vertices is an important research area for various types of networks [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. Cut vertex detection is crucial in various application scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in computer networks, the penetration of a virus can be prevented by simply taking a few critical nodes offline, thus ensuring normal network functionality for the rest of the network [8]. Moreover, the effect of a few critical nodes on the overall network connectivity was highlighted in [9], where removal of only 4% of the nodes in a Peer to Peer Gnutella Network resulted in major fragmentation of the whole network [10]. Finally in a wired telecommunications network, the identification of critical nodes can aid in jamming the network by suppressing the communication between a few critical nodes in the network [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in [3] it was observed that removal of 4% of the nodes in a Peer to Peer Gnutella Network resulted in major fragmentation of the whole network. The node criticality problem in Peer to Peer and overlay networks was also addressed in [4]. Finally, in [5] it was shown that in a telecommunication network, the penetration of a virus can be prevented by removing a few critical nodes.…”
Section: Introductionmentioning
confidence: 99%